PEMANFAATAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) BERDIKARI KAMPUNG TENUN PT. PERTAMINA PATRA NIAGA INTEGRATED TERMINAL PONTIANAK OLEH MASYARAKAT DI KELURAHAN BATU LAYANG KOTA PONTIANAK - Rahmat Arda; Pabali Musa; Indah Listyaningrum; Annisa Rizqa Alamri; Waskito Nugroho (KOMUNITAS, 2023)
This study describes and analyzes the allocation of social responsibility program target of PT. Pertamina Patra Niaga Integrated Terminal Pontianak and the utilization by the community in Batu Layang Substrict. This study was used the qualitative method with a descriptive approach. The techniques of data collection using observation, interview, and documentation. This study also used the componential analysis method to analyze the qualitative data. The results of this study is Berdikari Kampung Tenun CSR Program of PT. Pertamina Patra Niaga Integrated Terminal Pontianak in the social sector included education, health, and religion was not able to be classified as Corporate Social Responsibility because there had been no significant assistance to education, health and the environmental sector, the economic sector, has a significant positive impact on the people who are members of the Kampung Tenun Khatulistiwa Group.